Longitudinal sex and stress hormone profiles among reproductive age and post-menopausal women after severe TBI: A case series analysis. (20th March 2016) - Ranganathan, Prerna; Kumar, Raj G.; Davis, Kendra; McCullough, Emily H.; Berga, Sarah L.; Wagner, Amy K.
Abstract: Primary objectives : To describe hormone profiles for pre-/post-menopausal women, to monitor time to resumption of menstruation among pre-menopausal women and to describe cortisol associated LH suppression and phasic variation in other sex hormones over time Methods and procedures : This study determined amenorrhea duration and characterized acute (days 0–7) and chronic (months 1–6) gonadotropins [luteinizing hormone and follicle stimulating hormone (LH, FSH)], sex hormones (progesterone, estradiol) and stress hormone (cortisol) profiles. Women were pre-menopausal ( n = 3) or post-menopausal ( n = 3). Among pre-menopausal women, menstrual cycle resolution and phase association (luteal/follicular) was monitored using self-report monthly reproductive history questionnaires. This study compared post-TBI hormone profiles, stratified by menopausal status, to hormone levels from seven controls and described 6- and 12-month outcomes for these women. Main outcomes and results : Consistent with functional hypothalamic amenorrhea (FHA), menstruation resumption among pre-menopausal women occurred when serum cortisol normalized to luteal phase control levels. For post-menopausal women, serum cortisol reductions corresponded with resolution of suppressed LH levels. Conclusions : The stress of TBI results in anovulation and central hypothalamic-pituitary-ovarian (HPG) axis suppression. Future work will examine acute/chronic consequences of post-TBI hypercortisolemia and associated HPG suppression, the temporal association of HPG suppression with other neuroendocrine adaptations and how HPG suppression impacts multidimensional recovery for women with TBI.